2003
DOI: 10.1128/iai.71.3.1548-1550.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Zinc-Dependent Major Histocompatibility Complex Class II Binding Site of Streptococcal Pyrogenic Exotoxin C Is Critical for Maximal Superantigen Function and Toxic Activity

Abstract: The cocrystal structure of streptococcal pyrogenic exotoxin C (SPE C) with HLA-DR2a (DRA*0101,DRB5*0101) revealed a zinc-dependent interaction site through residues 167, 201, and 203 on SPE C and residue 81 on the β-chain of HLA-DR2a (DRA*0101,DRB5*0101). Mutation of these SPE C residues resulted in dramatically reduced biological activities. Thus, the zinc-dependent major histocompatibility complex II binding site is critical for maximal biological function of SPE C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…2C). These data suggest that there are two independent interfaces on SpeC responsible for the LG-2 cell aggregation phenotype, one that is represented by the zinc-dependent, high-affinity MHC II interface (6,29), and a second within the ␤-barrel domain that is consistent with characterized low-affinity MHC II interfaces (2)(3)(4)8).…”
Section: Lg-2 Cell Aggregation By the Spec Mutants Is Indicative Of Msupporting
confidence: 50%
See 3 more Smart Citations
“…2C). These data suggest that there are two independent interfaces on SpeC responsible for the LG-2 cell aggregation phenotype, one that is represented by the zinc-dependent, high-affinity MHC II interface (6,29), and a second within the ␤-barrel domain that is consistent with characterized low-affinity MHC II interfaces (2)(3)(4)8).…”
Section: Lg-2 Cell Aggregation By the Spec Mutants Is Indicative Of Msupporting
confidence: 50%
“…From the crystal structure of SpeC, the dimer interface occupied the generic, lowaffinity MHC II domain and thus precluded the low-affinity interaction (47). However, other work using limited mutational analysis has shown that SpeC likely possesses an alternative MHC II binding interface (29,48) analogous to the structurally characterized low-affinity interfaces of SEA, SEB and SEC 3 (2,4,8). Thus, to resolve the issue regarding the presence or absence of a potential low-affinity MHC II binding interface and to understand the molecular basis by which SpeC binds MHC II through this putative interface, we performed alanine-scanning mutagenesis of all SpeC residues within the ␤-barrel domain that could potentially contact MHC II.…”
Section: Generation Of the Spec Mutantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional Epitope Mapping on the Surface of the hV␤2.1 TCR for TSST-1 and SpeC-From prior co-crystallization studies (12,16,20,21), and using the wild-type hV␤2-TSST complex solved here, coupled with corroborating mutagenesis data (11,26,(33)(34)(35), supramolecular T cell activation complexes can be modeled for both TSST-1 and SpeC (Fig. 2).…”
Section: Resultsmentioning
confidence: 77%